Ways forward in transdisciplinary research: Insights from case studies on marine and coastal conflict transformations - Mello NGR; Christie P; Prado DS; Martins IM; Saunders F; Tafon R; Gilek M; Sowman M; Sander G; Dukes F; P Jacobi; Pierro B; et al. (Sustainable Futures)
Transdisciplinary research has been put forward as a means to foster a radical shift in traditional scientific paradigms by promoting knowledge democracy while tackling wicked problems. This paper analyses how local social-ecological dynamics and institutional realities affect the way in which transdisciplinary research generates knowledge and develops sustainability pathways in diverse marine and coastal conflict contexts. Drawing on a cross-case analysis from a multicountry Belmont Forum project, namely OceansPact, this research analyzes key lessons on transdisciplinary practice. This analysis is informed by online surveys, semi-structured interviews with scholars and focus group discussions with non-academic stakeholders involved in the OceansPact. The paper demonstrates that transdisciplinary approaches can foster conflict transformation. Nonetheless, the results highlight that context-specific factors, including trust-building strategies and institutional cultures, significantly shape the processes of knowledge co-production and linking knowledge to transformative action. This study hence emphasize the need of flexible approaches, instead of standardized frameworks, that accommodate these diverse contexts and power dynamics, warning against reductionist approaches that oversimplify complexity. Emphasizing the political nature of transdisciplinarity, this paper calls for mechanisms that mitigate power asymmetries in transdisciplinary spaces. This paper moreover underscores the urgent need of systemic changes in academic institutions to support long-term, equitable collaboration between scholars and non-academic stakeholders, as well as of a shared understanding of transdisciplinary research so that this model can drive positive transformation.